Legitimisation of Hindutya ideology in PM Modi's re-election campaign speeches : a sociocognitive discursive analysis - Abdullah, Iman Fathima Sheik (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
A right-wing, Hindu nationalist party, the Bharatiya Janata Party (BJP), altered the secular dynamics of Indian politics since their election in 2014. And the re-election of Prime Minister Narendra Modi in the 2019 general election raised the question of how Hindu nationalist ideology (Hindutva) permeated into mainstream politics. This study analysed thirteen of Prime Minister Modi’s speeches delivered during his re-election campaign in the state of Uttar Pradesh, the stronghold of the BJP. By employing the Socio-Cognitive Approach (SCA) as proposed by van Dijk (2016), this research accommodated Reyes' (2011) compilation of legitimisation strategies to identify the discursive strategies used to legitimise the Hindutva ideology. Additionally, the use of the metaphor CHOWKIDAR (translated as watchman or guardian) to aid the legitimisation was analysed by adopting the conceptual blending theory (CBT) model into the SCA framework. This study also briefly discussed the threat of Hindutva ideology being legitimised in Indian political discourse and the threat it posed to secular and liberal democracy. It can be concluded that Modi legitimised the Hindutva ideology in his re-election speeches through legitimisation strategies of emotions, rationalisation, presenting hypothetical futures, voices of expertise and altruism. Furthermore, this research offered a methodological contribution to van Dijk’s socio-cognitive approach by adopting tools from Cognitive Linguistics to better map the cognitive medium propounded in SCA